Genicular Nerve Radiofrequency Ablation for the Treatment of Painful Knee Osteoarthritis: Current Evidence and Future Directions. (23rd July 2021) - Conger, Aaron; Gililland, Jeremy; Anderson, Lucas; Pelt, Christopher E; Peters, Christopher; McCormick, Zachary L
Abstract: Genicular nerve radiofrequency ablation (RFA) is increasingly being performed to treat chronic pain due to knee osteoarthritis (KOA). This narrative review provides a concise summary of the relevant neuroanatomy, randomized controlled trials, appropriate patient selection, and safety relating to genicular RFA. Cadaveric studies demonstrate significant variability in the location of the genicular nerves, which has stimulated debate about the ideal target locations for genicular RFA. Despite this, favorable outcomes have been observed in studies targeting only the superior medial genicular nerve, inferior medial genicular nerve, and superior lateral genicular nerve. Several randomized controlled trials demonstrate superiority of genicular RFA compared with intra-articular steroid, viscosupplementation, and oral analgesics. Genicular RFA of the superior medial genicular nerve, inferior medial genicular nerve, and superior lateral genicular nerve appears to be an effective treatment for painful KOA, but targeting additional sensory nerves may further improve treatment success. Although genicular RFA appears relatively safe on the basis of the available data, additional large-scale studies are needed to provide greater confidence.